Shaping Future Muslims: Education, Creativity and Values - Syahril, Sulthan (International Journal on Advanced Science, Education, and Religion, 2025)
Islamic education in the modern era faces significant challenges in balancing the need for mastery of knowledge with the strengthening of character and spirituality. Learning models that are solely oriented towards memorization often fail to foster critical thinking, creativity, and the internalization of moral values ​​in students. Therefore, a more integrative approach is needed so that Islamic education not only produces a generation that is knowledgeable, but also creative and has noble character. This study aims to: (1) identify the role of Islamic education in developing critical thinking and creativity in students; (2) explore the core values ​​of Islam that are relevant in strengthening the character of the younger generation; and (3) offer a model of integration between education, creativity, and values ​​that can be implemented in educational institutions. The method used is a qualitative research based on literature review, by analyzing classical Islamic educational theory, contemporary approaches in education, and relevant research findings. The results show that Islamic education plays a significant role in shaping students who are capable of critical thinking, creativity, and religious character through the implementation of learning strategies based on dialogue, problem solving, and digital literacy. Islamic values ​​such as honesty, responsibility, justice, and spirituality are found to be highly relevant in building the character of the future Muslim generation. This study concludes that the integration of education, creativity, and values ​​is an important foundation in the development of Islamic education that is adaptive to the demands of the 21st century.